Aftermath of fortnightly universal testing for severe acute respiratory corona virus‐2 infection in maintenance hemodialysis patients. Issue 5 (24th June 2021) - Patel, Manas R.; Kushwaha, Ravi S.; Behera, Manas; Bhadauria, Dharmendra S.; Yachha, Monika; Kaul, Anupma; Prasad, Narayan
Abstract: Introduction: Asymptomatic maintenance hemodialysis patients with acute respiratory corona virus‐2 (SARS‐COV‐2) are missed with pre‐dialysis screening without testing. The possible ideal strategy of testing each patient before each shift with reverse transcription polymerase chain reaction (RT‐PCR) is not feasible. We aimed to study the effectiveness of fortnightly screening with RT‐PCR for SARS‐CoV‐2 in curbing transmission. Methods: Between July 1, 2020 and September 30, 2020, all 273 patients receiving hemodialysis were subjected to fortnightly testing for SARS‐Cov‐2 in the unit to detect asymptomatic patients. The cost and effectiveness of universal testing in preventing transmission were analyzed using susceptible‐infectious‐removed (SIR) modeling assuming R 0 of 2.2. Results: Of 273 MHD patients, 55 (20.1%) found infected with SARS‐CoV‐2 over 3 months. Six (10.9%) were symptomatic, and 49 (89.1%) asymptomatic at the time of testing. Six (10.9%) asymptomatic patients develop symptoms later, and 43 (78.2%) remained asymptomatic. A total of seven (6.1%) HCWs also tested positive for the virus. Fortnightly universal testing is cost‐effective, and SIR modeling proved effective in preventing person‐to‐person transmission. Conclusions: Repeated universal testing in maintenance hemodialysis patients detected 89% of asymptomatic SARS‐CoV‐2 patients over 3 months and appeared to be an effective strategy to prevent person‐to‐person transmission in the dialysis unit.